Marker pen writing of perovskite solar modules - Yuhao Song; Miaosen Yao; Chen Dong; Sergey Dayneko; Gaogeng Wang; Dongyang Zhang; Yingying Deng; Junjie Tong; Qichao Wang; Gentian Yue; Yueyue Gao; Weifeng Zhang; et al. (Nature Communications)
Abstract Solution-processed perovskite photovoltaics promise low-cost, lightweight, and wearable power sources. Processing techniques play a crucial role in this field. Here, we introduce a large-area, patternable, and cyclable film writing technique that utilizes marker pen as a fabrication tool. By adjusting ink concentration, pressure, writing speed, tip width, solvent engineering, and using fiber-capillary structure of marker pens, we demonstrate control over perovskite ink colloids, film thickness (from 200 to > 1000 nm) and area (from 1 to 100+ cm2) patterning on rigid and flexible substrates, as well as ambient writing of crystalline perovskite film. Marker pen written rigid and flexible carbon-electrode perovskite solar modules in mask- and laser-free manners achieve 16.3% and 14.5% power conversion efficiencies, respectively. This method offers an opportunity for rapid on-site fabrication of lightweight and deformable power sources on various substrates, including inflated elastic balloons and folded cellophane paper, and produces customizable irregular solar modules.